Integrating Primary Care, Home Care, and Community Health Services in Ontario - Sevrenne Sheppard (Health Reform Observer - Observatoire des Réformes de Santé, 2019)
The Patients First Act is the legislative piece of a large-scale reform in Ontario's health systems governance. Prior to 2017, home and community care in Ontario was managed by Community Care Access Centres (CCACs), which were overseen by Local Health Integration Networks (LHINs) in each region. Both the CCACs and the then provincial government had come under public criticism for inefficient spending, lack of coordination between health care providers, exacerbating existing inequalities with regards to home and community care, and adding an unnecessary layer of bureaucracy to an already strained health care system. The Patients First Act was introduced in 2016 in order to better integrate home and community care with primary care, and to improve efficiency, transparency, and continuity of care for patients. This organizational reform was achieved by abolishing the CCACs and transferring their duties to the LHINs, along with the authority to issue policy directives to other health services providers. The Patients First Act is a recent development in Ontario health systems reform, and ongoing evaluation is needed to determine the full impact of this policy. While the strengths of the Act include its focus on access and accountability for patients, there are significant gaps that remain to be addressed, including the role of LHINs in working with physicians and hospital boards, and in framing equity issues beyond geographical difference to include growing ethnocultural and linguistic diversity.